Object-oriented software development with fault tolerance for distributed real-time systems - Yau, S.S.; Wang, J.; Kim, J.-W. (Proceedings of WORDS'96 : the Second Workshop on Object-oriented Real-time Dependable Systems : February 1-2, 1996, Laguna Beach, California, USA, 1996)
An object oriented application software development approach with fault tolerance for distributed real time systems is presented. This approach is based on the Parallel Object Oriented Functional computation model (PROOF) with real time and fault tolerance features. The real time constraints are satisfied by using multi version methods, which are based on virtual method definitions with different underlying implementations, and encapsulation of time constraints in objects. The fault tolerance in application software layer is supported by monitoring, checkpoints and recovery.